Strengthening Community Resilience: Mapping Local Capacity to Mitigate Mount Merapi Eruption Risk in Dukun Sub-district, Indonesia - Ulya Zulfa Hanifah; Juhadi Juhadi (JPG (Jurnal Pendidikan Geografi), 2025)
This study aims to map community capacity in efforts to reduce the risk of Mount Merapi eruption disasters in Dukun Sub-district, Magelang Regency. The objectives include: (1) analyzing the threat levels and community capacity index; (2) examining efforts to enhance community capacity; and (3) mapping the levels of community capacity based on the Disaster-Prone Area (Kawasan Rawan Bencana/KRB) zones. A quantitative descriptive approach was employed with a cluster random sampling technique, based on KRB zoning (KRB I, II, and III). Data were collected through observation, questionnaires, and documentation, and analyzed using scoring and descriptive interpretation. The results show that the threat level is categorized as moderate in KRB I and high in KRB II and III. The community capacity index is generally at a moderate level across all zones; however, capacity in KRB I is categorized as moderate, while in KRB II and III it is low. These findings highlight the urgent need for more intensive strategies to strengthen community capacity, especially in high-risk areas.